Comparison of Different Cell Culture Media in the Model of the Isolated and Superfused Bovine Retina: Investigating the Limits of More Physiological Perfusion Solutions. (1st February 2018) - Hurst, José; Vitkute, Milda; Hofmann, Kathleen; Müller, Sebastian; Löscher, Marina; Bartz-Schmidt, Karl-Ulrich; Spitzer, Martin S; Schnichels, Sven; Januschowski, Kai
ABSTRACT: Purpose : The isolated superfused retina is a standardized tool in ophthalmological research. However, stable electroretinogram (ERG) responses can only be obtained for around eight hours; therefore, limiting its use. The aim of this study was to evaluate the short-term potential of different cell culture media and to promote long-term testing based on the results obtained. Materials and Methods : For the experimental procedure bovine retinae were prepared and perfused with the standard Sickel solution and an ERG was performed. After recording stable a- or b-waves, different media (Dulbecco's Modified Eagle's Medium (DMEM), MACS, and Neurobasal) were superfused for 45 minutes. ERG recovery was monitored overall for 75 minutes. Analysis of the mRNA expression of Thy-1, GFAP, Bax/Bcl-2-ratio, Rhodopsin, and Opsin via qRT-PCR was performed directly after ERG recording on the same retina. Results : None of the tested media had a negative effect on a-wave amplitudes, although b-wave amplitudes decreased (DMEM) or increased (MACS and Neurobasal) compared to the standard solution (Sickel) after 45 minutes of exposure. However, after 75 minutes of wash-out, no difference to the standard solution alone could be observed. Exposure to different media either had no effect or decreased the Opsin and Rhodopsin mRNA levels. Thy-1 expression was strongly diminished in DMEM and MACS (by 2–3-fold), whereas incubation in Neurobasal medium led to a slight increase compared to incubation with the standard solution. Furthermore, the Bax/Bcl-2 ratio indicated an anti-apoptotic effect ( Bax/Bcl-2 = 0.16; p < 0.05) for Neurobasal. Conclusion : Neurobasal medium displayed the best electrophysiological properties in the short-term and may be applicable for stable long-term escalation testing.